Ramuan Herbal Untuk Pengobatan Penyakit Perempuan dalam Naskah Tradisional Pulau Penyengat - Wahyuni, Indah; Widyatwati, Ken (Jumantara: Jurnal Manuskrip Nusantara, 2024)
The manuscript of Pengobatan Tradisional pada Masyarakat Pulau Penyengat (PTpMPP) contains various types of illnesses along with their herbal ingredients, one of which is illness related to women. This study aims to present the transliteration and editing of the text of the treatment of female diseases in the PTpMPP manuscript and explain the ethnomedicine studies contained therein. The methods used are data collection through field studies and literature studies, data processing through manuscript description, transliteration, and text editing, and data analysis using ethnomedicine theory. The main data source used is the PTpMPP manuscript in Jawi script and Malay language, kept at Yayasan Inderasakti, Penyengat Island as an authentic representation of local traditional medicine. The results of this study present an edited text with five causes of female illness, namely meroyan (ordinary), meroyan throughout the body, meroyan bleeding, meroyan oil to the liver, and women who do not menstruate. Each illness has its own herbs and medical practices used, belonging to the naturalistic medical system.